Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica) ... - Cantero, Álvaro L. Peña (Plazi.org taxonomic treatments database, 2021)
This dataset contains the digitized treatments in Plazi based on the original journal article Peña Cantero, Álvaro L. (2021): Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica). Zootaxa 4966 (3): 321-336, DOI: https://doi.org/10.11646/zootaxa.4966.3.4 ...